Konstruksi Pengembangan Wakaf Saham Dalam Rangka Mengoptimalkan Potensi Wakaf Produktif di Indonesia - Nasution, Lokot Zein; Aris, Diba Anggraini (Islamic Circle, 2020)
Waqf has an important role for improving the quality of development, especially through improving social and economic dimensions. However, the management of waqf on average has not been able to be productively, so that its role for development is still not optimal. This is caused the suboptimal innovation and governance of waqf. The strategy to improve innovation in waqf governance is to create product diversification, one of which is stock waqf. However, the development of stock waqf is constrained by the lack of literature references so that the exploration of the potential and impact of stock waqf is still unknown. Therefore, the purpose of this study is to construct the development of stock waqf in order to optimize the potential of productive waqf in Indonesia. Based on the desk study approach analyzed through literature review, three discussion results can be drawn, namely: (i) the community still has a weak level of knowledge related to stock waqf, which is caused by socialization and literacy that are still low; (ii) the position of stock waqf in the constellation of Islamic financial ecosystem is still weak; and (iii) there are two models of implementing stock waqf that can be done, namely waqf that comes from the profits of stock investors, and waqf that makes Islamic stocks as an object of waqf. To construct the development of stock waqf, policy strengthening is needed, which includes the authorities of the Ministry of Finance, the Ministry of Religion, BWI, BI, and OJK.